2014
DOI: 10.1016/j.egypro.2014.10.262
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Hydraulic Design of a Solar Collector Field for a Primary School Pool

Abstract: The methodology and results of the thermal and hydraulic design for a solar heating field of an elementary school's semi-olympic pool is presented. Improved flat solar collectors with copper tube and aluminum fins were used. From own experiences, many Mexican solar fields do not operate correctly because of their poor flow balance (irrigation) , may be due to lack of attention given to this aspect. That's why the research of this work focuses on studying the behavior of the pressure drop in a hydraulic arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Furthermore, the different solar collector types, the different designs of the solar collector fields, the different control strategies including the different flow rates and maybe the different uneven flow distributions in the solar collector fields will influence the thermal performance. For instance, (Bava and Furbo, 2016) showed that the flow rate will influence the flow distribution and efficiency of solar collectors and (Rohde and Knoll, 1976), (Dorantes, Garcia, Salazar, Oviedo, Gonzalez, Alanis, Salazar and Martin-Dominguez, 2014) and (Bava and Furbo, 2017) showed that the flow rate influence the flow distribution and thermal performance of a solar collector field. Figure 3.…”
Section: Measured Yearly Thermal Performances Of Solar Collctor Fieldsmentioning
confidence: 99%
“…Furthermore, the different solar collector types, the different designs of the solar collector fields, the different control strategies including the different flow rates and maybe the different uneven flow distributions in the solar collector fields will influence the thermal performance. For instance, (Bava and Furbo, 2016) showed that the flow rate will influence the flow distribution and efficiency of solar collectors and (Rohde and Knoll, 1976), (Dorantes, Garcia, Salazar, Oviedo, Gonzalez, Alanis, Salazar and Martin-Dominguez, 2014) and (Bava and Furbo, 2017) showed that the flow rate influence the flow distribution and thermal performance of a solar collector field. Figure 3.…”
Section: Measured Yearly Thermal Performances Of Solar Collctor Fieldsmentioning
confidence: 99%
“…In most of the mentioned studies, the collector field was only a part of the entire system and hence was treated with little detail, usually by a single collector component. Consequently, aspects such as flow distribution across the collector field are not considered, although they may have an impact on the collector field performance (Dorantes et al, 2014). This is especially valid nowadays, when the collector fields have become increasingly larger.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Uniform flow distribution is of great importance also for the efficient operation of the entire collector field, but it is often overlooked (Dorantes et al, 2014). Ideally, the layout of a collector array should keep the pipe lengths as short and the flow distribution as uniform as possible.…”
Section: Literature Reviewmentioning
confidence: 99%